2013
DOI: 10.14573/altex.2013.4.427
|View full text |Cite
|
Sign up to set email alerts
|

Generation of genetically-modified human differentiated cells for toxicological tests and the study of neurodegenerative diseases

Abstract: Summary -phenylpyridinium (MPP + ). Different lentiviral constructs then were tested: cells labeled ubiquitously with green (GFP) or red fluorescent protein (RFP) allowed the quantification of neurite growth and of its disturbance by toxicants; expression of proteins of interest could be targeted to different organelles; production of two different proteins from a single read-through construct was achieved successfully by an expression strategy using a linker peptide between the two proteins, which is cleaved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 58 publications
1
70
0
Order By: Relevance
“…Schildknecht et al have recently reported a stable α-synuclein-overexpressing LUHMES subclone [32] . In their characterization, the increased amount of α-synuclein in LUHMES cells was well tolerated and no cytotoxicity was observed after overexpression of α-synuclein.…”
Section: Wwwnaturecom/apsmentioning
confidence: 99%
“…Schildknecht et al have recently reported a stable α-synuclein-overexpressing LUHMES subclone [32] . In their characterization, the increased amount of α-synuclein in LUHMES cells was well tolerated and no cytotoxicity was observed after overexpression of α-synuclein.…”
Section: Wwwnaturecom/apsmentioning
confidence: 99%
“…This human dopaminergic precursor cell line allows the generation of homogeneous, fully postmitotic dopaminergic neuron cultures. 28, 29 …”
mentioning
confidence: 99%
“…Transfection of differentiated Luhmes cells has been described previously (Schildknecht, et al, 2013). Briefly, cells were pre-differentiated for 2 days.…”
Section: Methodsmentioning
confidence: 99%